Managing Households' Expectations with Salient Economic Policies - Francesco D'Acunto; Daniel Hoang; Michael Weber (Center for Economic Studies and ifo Institute (CESifo), 2019)
The empirical effectiveness of economic policies that operate theoretically through similar channels differs substantially. We document this fact by comparing an easy-to-grasp expectations-based policy, unconventional fiscal policy, with a policy whose implications are harder to understand by non-expert consumers, forward guidance. Both policies aim to stimulate consumption via managing inflation expectations based on the Euler equation. Unconventional fiscal policy uses trivial announcements of future consumer-price increases to boost inflation expectations and consumption expenditure on impact. Instead, forward guidance requires that agents understand the inflationary effects of future low interest rates to increase their inflation expectations and spending today. We find households' inflation expectations and readiness to spend react substantially to unconventional fiscal policy announcements. The reaction is homogeneous across households with different levels of sophistication. Instead, households do not react after forward guidance announcements. These results support recent work stressing the importance of limited cognition for the effectiveness of policies.
Keywords: D12; D84; D91; E21; E31; E32; E52; E65; 330; expectations; natural experiments; consumption; fiscal policy; monetary policy; macroeconomics with micro data